2010
DOI: 10.1186/1756-0500-3-305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5 novel germline APC mutations and characterization of clinical phenotypes in Japanese patients with classical and attenuated familial adenomatous polyposis

Abstract: BackgroundFamilial adenomatous polyposis (FAP) is an autosomal dominant hereditary disease characterized by multiple colorectal adenomatous polyps and frequent extracolonic manifestations. An attenuated form of FAP (AFAP) is diagnosed based on a milder colorectal phenotype, and the colorectal phenotype of (A)FAP has been linked to germline APC mutations. The relationships between the spectrum of mutations and extracolonic manifestations are quite well known, but they need to be further defined.FindingsNine ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…The variant lacking exon 15 has been reported to cause quantitative distortion of mRNA isoforms both in the splice acceptor site mutant and in a germline mutation at the last nucleotide of exon 15 (6). The latter diagnosed case revealed over 300 colorectal polyps at 32 years of age, including colorectal cancer, multiple gastroduodenal adenomas and duodenal adenocarcinoma (6). Quantitative distortions of mRNA isoforms were also observed in the present case.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The variant lacking exon 15 has been reported to cause quantitative distortion of mRNA isoforms both in the splice acceptor site mutant and in a germline mutation at the last nucleotide of exon 15 (6). The latter diagnosed case revealed over 300 colorectal polyps at 32 years of age, including colorectal cancer, multiple gastroduodenal adenomas and duodenal adenocarcinoma (6). Quantitative distortions of mRNA isoforms were also observed in the present case.…”
Section: Discussionsupporting
confidence: 57%
“…Varesco et al (7) indicated that a splice donor site mutation on exon 10 was associated with late-onset FAP, which is a milder form of the disease. The variant lacking exon 15 has been reported to cause quantitative distortion of mRNA isoforms both in the splice acceptor site mutant and in a germline mutation at the last nucleotide of exon 15 (6). The latter diagnosed case revealed over 300 colorectal polyps at 32 years of age, including colorectal cancer, multiple gastroduodenal adenomas and duodenal adenocarcinoma (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no difference has been observed between gastric or duodenal location of the polyps and mutation sites [19]. With regard to the subtype, mutations in exons 10-15H (codon 564-1,465) have been seen with a significantly higher frequency in GAs yet are undetected in FGPs [20].Finally,afewstudieshavereportedmutationalvariation in dysplastic and malignant FAP-associated gastric polyps, with rare KRAS mutations in codon 12 seen in FGPs harboring low grade [21] and mutations in exon 4 of the FAP gene reported in gastric polyposis and early-onset gastric carcinoma in AFAP patients [22].…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…esis of this patient, genetic alterations of the germ-line and somatic genes were examined [16] . Sequencing of the germline APC gene revealed a transition from ACG to ATG at codon 499 in exon 11.…”
Section: A B C Dmentioning
confidence: 99%